Cerebral Lactate Concentration in Neonatal Hypoxic-Ischemic Encephalopathy: In Relation to Time, Characteristic of Injury, and Serum Lactate Concentration - Wu, Tai-Wei; Tamrazi, Benita; Hsu, Kai-Hsiang; Ho, Eugenia; Reitman, Aaron J.; Borzage, Matthew; Blüml, Stefan; Wisnowski, Jessica L. (Frontiers in Neurology, 2018)
Background: Cerebral lactate concentration can remain detectable in neonatal hypoxic-ischemic encephalopathy(HIE) after hemodynamic stability. The temporal resolution of regional cerebral lactate concentration in relation to the severity or area of injury is unclear. Furthermore, the interplay between serum and cerebral lactate in neonatal HIE has not been well-defined. The study aims to describe cerebral lactate concentration in neonatal HIE in relation to time, injury, and serum lactate. Design/Methods: Fifty-two newborns with HIE undergoing therapeutic hypothermia(TH) were enrolled. Magnetic resonance imaging and spectroscopy (MRI+MRS) were performed during and after TH at 54.6 ± 15.0 and 156 ± 57.6 hours of life, respectively. Severity and predominant pattern of injury was scored radiographically. Single-voxel 1H MR spectra were acquired using short-echo (35 ms) PRESS sequence localized to the basal ganglia(BG), thalamus(Thal), grey matter(GM), and white matter(WM). Cerebral lactate concentration was quantified by LCModel software. Serum and cerebral lactate concentrations were plotted based on age at time of measurement. Multiple comparisons of regional cerebral lactate concentration based on severity and predominant pattern of injury were performed. Spearman’s Rho was computed to determine correlation between serum lactate and cerebral lactate concentration at the respective regions of interest. Results: Overall, serum lactate concentration decreased over time. Cerebral lactate concentration remained low for less severe injury and decreased over time for more severe injury. Cerebral lactate remained detectable even after TH. During TH, there was a significant higher concentration of cerebral lactate at the areas of injury and also when injury was more severe. However, these differences was no longer observed after TH. There was a weak correlation between serum lactate and cerebral lactate concentration at the BG(rs =0.3,p=0.04) and Thal(rs =0.35, p=0.02). However, in infants with moderate-severe brain injury, a very strong correlation exists between serum lactate and cerebral lactate concentration at the BG(rs=0.7,p=0.03), Thal(rs=0.9p=0.001), and GM(rs=0.6,p=0.04) regions. Conclusion: Cerebral lactate is most significantly different between regions and severity of injury during TH. There is a moderate correlation between serum and cerebral lactate concentration measured in the deep grey nuclei during TH. Differences in injury and altered regional cerebral metabolism may account for these differences.